2014
DOI: 10.1111/geb.12183
|View full text |Cite
|
Sign up to set email alerts
|

Diverse responses of forest growth to drought time‐scales in theNorthernHemisphere

Abstract: Biosketchs: Sergio M. Vicente-Serrano is a climatologist focused in the development of methods and tools to improve drought quantification and monitoring, and the analysis of hydrological, agricultural and ecological impacts of drought. J. Julio Camarero is a dendroecologist and plant ecologist interested on the analyses of growth and regeneration patterns of woody plants in response to global change. César Azorín-Molina is a climatologist interested in the study of extreme weather events and their impacts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 42 publications
(66 reference statements)
2
83
0
1
Order By: Relevance
“…; Martin‐Benito, Beeckman & Canellas ; Mendivelso et al . ; Vicente‐Serrano, Camarero & Azorin‐Molina ; data downloaded from the Global SPEI data base: http://sac.csic.es/spei/database.html). Based on the climate data of the Climatic Research Unit of the University of East Anglia, the SPEI is calculated as the monthly difference between precipitation and potential evapotranspiration (see Vicente‐Serrano, Begueria & Lopez‐Moreno for more details) and has a spatial resolution of 0.5° of latitude and longitude.…”
Section: Methodsmentioning
confidence: 99%
“…; Martin‐Benito, Beeckman & Canellas ; Mendivelso et al . ; Vicente‐Serrano, Camarero & Azorin‐Molina ; data downloaded from the Global SPEI data base: http://sac.csic.es/spei/database.html). Based on the climate data of the Climatic Research Unit of the University of East Anglia, the SPEI is calculated as the monthly difference between precipitation and potential evapotranspiration (see Vicente‐Serrano, Begueria & Lopez‐Moreno for more details) and has a spatial resolution of 0.5° of latitude and longitude.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Stephenson [96] showed that the evapotranspiration deficit is a better metric than precipitation for explaining the current distribution of vegetation communities at the global scale. Moreover, the SPEI is computed on different time scales, enabling identification of the most suitable time scale to detect the varied response times of vegetation communities to water deficits [30,97]. This approach is undoubtedly preferable to identifying drought impacts on vegetation activity and growth based on annual precipitation, and has usually been used in studies analyzing the influence of climate on the NDVI in semiarid regions [98][99][100].…”
Section: Influence Of the Drought Variability On Vegetation Activitymentioning
confidence: 99%
“…Los valores que toma el SPEI para la determinación de episodios secos son los mismos que el SPI (Tabla 1). Este índice ha sido ampliamente aceptado y utilizado en estudios de sequía a muy diversas escalas (Vicente-Serrano et al, 2014a;Manatsa et al, 2015;Naumann et al, 2015;Blauhut et al, 2015;Stagge et al, 2015aStagge et al, , 2015bDas et al, 2016;Rhee and Cho, 2016;Yang et al, 2016).…”
Section: íNdice Estandarizado De Precipitación Y Evapotranspiración (unclassified